Students’ Self-Efficacy and English-Speaking Skills in Advanced Speaking Class: Do They Correlate? - Wijayanti, Yelli; Kher, Dinovia Fannil (Universitas Negeri Padang, 2024)
This research aims to determine the correlation between students' self-efficacy and English-speaking skills at Advanced Speaking. This research was a correlational design. The population of this research is the English Literature Department 2022 Universitas Negeri Padang from NK2-NK5, and the sample is the NK 2 class which was chosen by using cluster random sampling. The instruments of this research were a Self-efficacy questionnaire and a speaking test, and the data were analyzed using SPSS 25 for Windows. The data were analyzed using the Spearman Rank test. It was found that the sig. (2 tailed) 0.454 higher than sig. 0.05. As a matter of fact, the null hypothesis was accepted. Therefore, the results of this research showed that there was no correlation between self-efficacy and students’ speaking skills in Advanced Speaking classes.